Implementation of Interactive Learning Video Media to Improve Science (IPAS) Learning Outcomes on the Topic of the Properties of Light for Fourth-Grade Students at MI At-Taufiq Samarinda - Siti Hannan; Amalia Shofa; Maryani Utarie (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the implementation of interactive video learning media and analyze its impact on improving science and social studies (IPAS) learning outcomes, specifically on the topic of light properties, among fourth-grade students at MI At-Taufiq Samarinda. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted over two cycles, each comprising planning, action, observation, and reflection stages. The subjects were 23 fourth-grade students. Data were gathered through evaluation tests, classroom observation, and interviews. Results revealed significant improvements: the class average rose from 66.52 in the pre-cycle to 78.26 in Cycle I and further to 88.48 in Cycle II. Learning mastery rates increased from 21.74% to 82.61% and ultimately reached 100%. These findings confirm that the use of interactive video learning media is effective in enhancing student understanding and academic performance on the light properties topic.